equate each term of the denominator to zero to get three different values of x. Now leaving out the term containing the particular value of x, substitute for x in all the other terms of the given equation to obtain respective constant for the term in the second equation.

i.e. Equating (x + 2) to zero we obtain x + 2 = 0 ==> x = -2

Now substituting for x in the first equation by (-2) we obtain the constant A.

The above steps can be put in the form of a few simple formula as

the partial fractions can be written as

### Like this:

Like Loading...

*Related*